The effect of amorphous rice husk silica to the polysulfone membrane separation process - Harun, Zawati (2013)
This study investigates the effect of additive rice husk silica and Polyethylene glycol (PEG) on the performance of polysulfone (PSf) membrane. The membrane was prepared by phase inversion method using PSf, N-methyl-2-pyrrolidone (NMP) and rice husk silica was added as an additive. The performance of the membrane was analyzed by using distilled water for permeation test and humic acid for the rejection test. The result showed that the hydrophilic of PSf/PEG membrane has significantly improved the permeation and rejection performance with addition of rice husk silica. The results showed that with addition of 3% rice husk silica give the highest rejection flux at 196.63 L/m2hr with the rejection value 98%.